Lip, a Human Gene Detected by Transfection of DNA From a Human Liposarcoma Encodes a Protein With Homology to Regulators of Small G Proteins. (1998) - Patterson, Helen; Gill, Sandra; Benjamin, Harry; Mitchell, Philip J.; Cooper, Colin S.
Abstract : Purpose/Method. Transfection experiments have been used to identify activated oncogenes in a wide variety of tumour types. Here we describe the use of transfection experiments utilizing DNA from a human pleomorphic liposarcoma to identify a novel gene, designated lip which maps to chromosome 19. Results. lip was expressed in all sarcoma cell lines examined and a wide variety of normal tissues. Sequencing of cDNAs prepared from transcripts of the normal lip gene indicates that lip is predicted to encode a 966 amino acid protein with a region of homology to proteins such as vav, dbl, lbc and ect-2 which act as GDP–GTP exchange factors for the RAS superfamily of small GTP-binding proteins, and the N-terminal 830 amino acids are identical to the recently identified gene p115-RhoGEF, an exchange factor for RHOA. In transfectants, lip has undergone a rearrangement which results in C-terminal truncation of the predicted LIP protein. However, we failed to detect this alteration in the primary liposarcoma used in the original transfection experiments, or in other sarcoma specimens examined. Discussion. When considered together, these observations suggest that transforming lip sequences represent an alternatively spliced form of p115-RhoGEF that is activated for transformation by C-terminal truncation during transfection, and is not widely involved in sarcoma development.